A Semiotic Analysis of Male Body Treatment Product Advertisements as Found on the Internet - Zuldianof Zuldianof (Vivid: Journal of Language and Literature, 2015)
This study is a semiotic analysis of male body treatment product advertisements as found on the internet. Sign is tronsformed into the order signification, as explained by Barthes. The aim of the reseach is to explain the meaning of denotation and of linguistic and non linguistic signs in the data..The data sources are 8 advertisements, taken from internet based on three categories; they contain linguistic and non linguistic signs, the brands used to be associated to women, and then they start to produce a specific variant for men recently. These data are classified based on the linguistic and non linguistic signs. The method in collecting the data is non participant observational method. After that, the analysis is done by using the order of signification from Barthes in order to find the denotative and connotative meanings. The data are analysed by applying referential method, and the result of the analysis is presented by applying formal and informal form.From the result of the analysis, it is known that the advertisers try to create new image about the products. The products were known as a body treatment product associated with women, beauty and motherhood in the early years. Now, they launched a new variant specific to men, which are always associated with power, bravery, and fatherhood. By using linguistic signs, and supported by non linguistic signs, the advertisers put masculinity values into body treatment products, which are actually aimed to create beauty values. Camouflage occurs by controlling public opinion that body treatment products is needed by men to improve their performance and activities.Keywords: linguistic sign, non linguistic sign, order of signification, male body treatment product